Platelets from Calreticulin mutated essential thrombocythemia patients are less reactive than JAK2 V617F mutated platelets. Issue 4 (8th January 2020) - Hauschner, Hagit; Bokstad Horev, Melanie; Misgav, Modi; Nagar, Meital; Seligsohn, Uri; Rosenberg, Nurit; Koren‐Michowitz, Maya
Abstract: Both JAK2 V617F and calreticulin ( CALR) mutated essential thrombocythemia (ET) patients have different clinical characteristics, with lower thrombosis risk in patients with CALR mutations. To elucidate the mechanism for this lower risk we studied platelet function in ET patients with either JAK2 V617F or a CALR mutation. Platelet activation state was similar in ET and healthy controls at baseline using P‐selectin and PAC1 flow cytometry analysis. However, CALR mutated platelets were significantly less activated following ADP stimulation, compared to control or JAK2 mutated platelets ( P < .001). In live‐cell imaging of platelet attachment to immobilized fibrinogen by Interference Reflection Microscopy (IRM), the number of attached CALR mutated platelets was lower compared to control and JAK2 mutated platelets, with lower fractions of platelets achieving the fully spread state (90%, 78% and 54% of adherent cells for control, JAK2 and CALR mutated subjects, respectively). Compared to controls, ET patients, regardless of the mutation type, had increased numbers of immature platelets (IP) and leukocyte platelet aggregates (LPA), as well as plasma sP‐selectin. These were all correlated with the platelet count and not to the state of platelet activation. We also found that intracellular free Ca 2+ was increased in resting ET compared to control platelets. Note, CALR had a more dispersed localization in activated ET platelets compared to healthy controls, and mutated CALR interact physically with TpoR in CALR mutated platelets. We hypothesize that defects in platelet activation and spreading in CALR mutated patients can explain, at least in part, the lower thrombotic tendency in CALR mutated ET patients.